Bioprospecting studies: Transforming the natural genetic heritage into biotechnological richness - Maester, Thais Carvalho [UNESP]; Gomes, Elisângela Soares [UNESP]; Pereira, Mariana Rangel [UNESP]; Sierra, Elwi Guillermo Machado [UNESP]; Lemos, Manoel Victor Franco [UNESP]; de Macedo Lemos, Eliana G. [UNESP] (Springer Nature, 2017)
The Brazilian microbiota has great potential richness for industrial use, given its mega-diversity. Despite the advances in international research that have provided access to such microbiota, via several approaches (metagenomics; second- generation DNA sequencing, in situ cultivation, and as a consequence high-throughput screening, etc.) a glimpse into the research output in Brazil demonstrates that such immense potential has been poorly explored. Even though the Brazilian scientific community has reached a degree of international excellence in research recognition, there is still strong centralization of knowledge and of biotechnology enterprises in the Southeast Region of the country, which greatly limits access to our multitude of biomes and ecosystems. Another problem is the lack of communication between the knowledge generation centers and practical efforts in the field, resulting in very little national intelligence reaching the consumer market. Consequently, the internal biotechnology market prioritizes imports, even though there are available domestic resources to generate competitiveness at a global level. Academic and industry integration initiatives through innovative agencies have demonstrated a path to bridge the gap between the ownership and the usage capacity of the country's rich microbial diversity.